Tetramates as antibacterial and anticancer core scaffolds - Cullere, L (2016)
This thesis is concerned with the synthesis of small molecules that mimic tetramate- and pyrrolidinone-containing natural products, and the evaluation of their antibacterial and anticancer properties. Chapter 1 exposes the need for new antibiotics due to the emergence of resistance to current drugs, and it discusses the value of the natural product inspired approach for drug discovery. It also gives an overview of the structure, synthesis and biological properties of the natural products pramanicin and oxazolomycin, both of which contain a pyrrolidinone core. Chapter 2 describes an efficient synthetic route which allowed the preparation of a library of acyltetramates via Grignard addition to a Weinreb amide. This route was also used to prepare mimics of the acyl chain of pramanicin, comprising dienones and epoxy-enones of different lengths, and of the left-hand segment of oxazolomycin. In Chapter 3, reduction of the tetramate core of different closely-related systems was performed, and it was found that the diastereochemical outcome could be controlled by appropriate choice of substituents in the bicyclic system. Preparation of reduced acyltetramates was only successful via hydrogenation of the Weinreb amide and subsequent Grignard substitution. Chapter 4 describes the introduction of β-lactones to pyrrolidinones. Conditions for the selective formation of either spiro- or fused-β-lactones were found, which relied on the activation of the precursor β-hydroxyacid, accessed via N,O-acetal deprotection and ester saponification of the bicyclic systems. Further functionalisation of these analogues to mimic oxazolomycin was thwarted by the instability of some of the intermediates. Finally, the biological properties of the analogues are discussed in Chapter 5. The antibacterial activity against Gram-negative E. coli and Gram-positive S. aureus was examined using the holeplate method, which showed that the aliphatic lipophilic tetramates were the most potent inhibitors, with selective Gram-positive activity. An anticancer high-content screen was also designed, but only weak activities of the synthesised compounds were observed against four cancer cell lines.